The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.7863/jum.1997.16.6.401
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the fetal forehead and normative dimensions developed by three-dimensional ultrasonographic technology.

Abstract: Sonographic imaging of the fetal face is important since a number of chromosomal aberrations are associated with facial malformations. In the past, imaging of the fetal forehead and diagnosis of frontal bossing had been based on subjective evaluation using two‐dimensional ultrasonography. The purpose of this study was to evaluate quantitatively the fetal forehead using three‐dimensional technology to generate normative data throughout gestation. This should allow the objective diagnosis of abnormal growth of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Cleft lips, micrognathia, malformed ears, and frontal bossing have all been reported to be better displayed by 3DUS. [16][17][18][19][20][21][22][23] To our knowledge, the use of 3DUS in a fetus with congenital epulis has not been reported. In addition to providing a surface-rendered display of the mass, which facilitated parental counseling, the 3DUS images showed a high likelihood of functional impairment of the nasal airway because the mass was seen obstructing both nares.…”
Section: Discussionmentioning
confidence: 99%
“…Cleft lips, micrognathia, malformed ears, and frontal bossing have all been reported to be better displayed by 3DUS. [16][17][18][19][20][21][22][23] To our knowledge, the use of 3DUS in a fetus with congenital epulis has not been reported. In addition to providing a surface-rendered display of the mass, which facilitated parental counseling, the 3DUS images showed a high likelihood of functional impairment of the nasal airway because the mass was seen obstructing both nares.…”
Section: Discussionmentioning
confidence: 99%
“…The plaque is heterogeneous, with calcified regions casting a shadow on the common carotid artery. (b) The same image has been volume rendered to obtain a view of the vessel wall and the surface of the plaque (arrows) Volume measurement accuracy with three-dimensional ultrasound An important advantage of 3D US imaging is that it provides the ability to measure organs or lesions in arbitrary orientations [19,20]. Since conventional US imaging produces only 2D images, the volume is estimated from measurements of diameter in a few user-selected planes and assuming some idealized shape, resulting in inaccuracy and variability.…”
Section: Volume Rendering Techniques (Vr)mentioning
confidence: 99%
“…Cleft lips, micrognathia, malformed ears, and frontal bossing have all been reported to be better displayed and analyzed by 3DUS. [39][40][41][42][43][44][45][46][47][48] Cleft lip and palate is the most common craniofacial malformation; the value of 3DUS, compared with 2DUS, for the detection of this anomaly has been studied. 45,46,49,50 Investigators have shown that multiplanar imaging is best used to evaluate the extent of cleaving into the anterior alveolar ridge (Fig.…”
Section: Fetal Dysmorphologymentioning
confidence: 99%